IMPLEMENTASI AKREDITASI PROGRAM STUDI BERBASIS 9 KRITERIA MENUJU PERINGKAT UNGGUL (Studi Kasus di Program Studi Pendidikan Matematika IAIN Ambon dan Program Studi Pendidikan Matematika UIN Raden Intan Lampung) - Djaffar Lessy; Dinar Riaddin; Nanang Supriadi; Nurlaila Sehuwaky (Idaarah: Jurnal Manajemen Pendidikan, 2022)
This research aims to see the extent to which the implementation of study program accreditation based on 9 criteria in two different study programs ranked at the last accreditation, namely the Mathematics Education study program at IAIN Ambon and the Mathematics Education study program at UIN Raden Intan Lampung. The research method used is a comparative qualitative method, namely analyzing to find and find similarities and differences in phenomena. Data collection techniques in this study were interviews and documentation. The research results are described qualitatively in the form of advantages, disadvantages, similarities and differences in the implementation of 9 criteria-based accreditations in the two study programs. The results showed that the two study programs had fulfilled many of the 9 criteria-based accreditation assessment items. On the other hand, there are several items of accreditation assessment from each assessment criteria that have not been fully met by the two study programs.